Intermediate and deep ocean current circulation in the Mozambique Channel: New insights from ferromanganese crust Nd isotopes - Charles, Claire; Pelleter, Ewan; Révillon, Sidonie; Nonnotte, Philippe; Jorry, Stephan; Kluska, Jean-michel (Marine Geology, 2020)
The Mozambique Channel plays a key role in the exchange of water masses between the Indian and Atlantic Oceans, which include the North Atlantic Deep Water (NADW) inflow from the south and the North Indian Deep Water (NIDW), an aged form of the NADW spreading poleward from the northern and equatorial Indian Ocean basin. Several authors assume that the Davie Ridge acts as a topographic barrier to the northward advection of NADW, which would therefore be absent in the Comoros Basin. Other studies suggest that the NADW flows from the south of the Mozambique Channel to the Comoros Basin, indicating that the Davie Ridge may not currently constitute a blocking topographic barrier to deep water mass circulation. To address this question, we studied ferromanganese (Fe, Mn) crusts collected over 2000 km in the Mozambique Channel, from the Agulhas Plateau to the Glorieuses Islands. Neodymium (Nd) isotope compositions (εNd) of surface scrapings range between εNd = −10.1 above the Agulhas Plateau, which might reflect the NADW inflow, and more radiogenic values between εNd = −8.0 and − 8.2 in the Glorieuses area, highlighting the NIDW influence. However, value of εNd = −9.4 measured north of the Davie Ridge cannot be explained by the sole influence of the NIDW and therefore highlights the advection of the NADW northeast of the Comoros Basin. We estimate that the contribution of the NADW through the channel is up to 68% in the Agulhas Plateau and 60% north of the Davie Ridge. These findings are consistent with previous hydrographic studies and suggest that the Davie Ridge does not currently act as topographic barrier to deep currents.